OPTIMALISASI POTENSI LOKAL PAMELO: FORMULASI DAN ANALISIS KELAYAKAN EKONOMI CAMILAN SEHAT INOVATIF UNTUK PEMBERDAYAAN EKONOMI KREATIF PEREMPUAN DI DEWITAN - Muhammad Syakib Asqalani Rifai; Pandu Sapto Desmantyo; I Gusti Ayu Citra Dewi; Manda Rahmat Husein Lubis; Rochmah Dewi Suryani (Media Bina Ilmiah, 2025)
Pamelo (Citrus maxima) is a leading local commodity in Cibiru Wetan Village, Bandung Regency, rich in vitamin C, dietary fiber, and antioxidants. However, its utilization remains limited to fresh consumption and has not been optimally directed toward producing value-added processed products. This study aims to develop healthy snacks based on pamelo using food dehydrator technology, analyze their economic feasibility, and design a participatory and sustainable business model based on women-led creative economy in rural communities. The research employed an experimental approach that included the analysis of raw material potential, prototype development in three product variants (chips, snack bars, and cookies), sensory evaluation by 30 semi-trained panelists, as well as market surveys and business feasibility analysis. Results showed that pamelo chips obtained the highest scores for texture and overall acceptability. Economic analysis indicated an average profit margin of 38%. Additionally, a zero-waste approach was applied by utilizing pamelo peel and pith as supplementary ingredients. The findings demonstrate that the integration of food technology with local creative economic empowerment constitutes an innovative and effective strategy for developing adaptive and sustainable village-based food industries rooted in regional potential